Pengaruh Iklan Shopeefood Terhadap Minat Beli Konsumen Pada Remaja Palembang - Muhammad Nurfatoni; Hasmawati Fifi; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2024)
The writing of this research is motivated by technological advances in business development which cause tighter competition in various media. Various companies in developing their business carry out several advantages and advantages of each which aim to attract consumer shopping interest, one of which is the e-commerce company Shopee in promoting its products through advertisements on the Youtube internet-based media. For this reason, researchers are interested in examining the variables that can influence buying interest in consumers. The title of this research is "The Effect of Shopeefood Advertising on Consumer Purchase Interest in Palembang Teenagers". This study aims to determine the effect of Shopeefood advertisements on Youtube on buying interest in teenagers in Talang Kelapa Village, Palembang city. This type of thesis research is explanatory using quantitative methods. The technique used in sampling used the slovin formula with simple random sampling technique, with a sample size of 90 teenage respondents in Talang Kelapa Village Palembang. Based on the simple linear regression analysis test conducted, it shows that each unit of Shopeefood advertising has an increase in purchase intention of 1.185, which means it has a significant influence. Meanwhile, based on the hypothesis test tested through the correlation coefficient, it has a very strong relationship with a value of 0.948, greater than the Ftable value of 0.207 (degree of freedom) at a significant level of 5% (0.05) with a positive direction, so that researchers can conclude that H0 is rejected while H1 is accepted. This statement is also supported based on the results of the coefficient of determination analysis, where the R Square value is 0.920 with a percentage of 92%. In other words, there is an influence of Shopeefood advertising on consumer buying interest among teenagers in Talang Kelapa Palembang Village with the percentage of influence on variable X (Shopeefood advertising) on variable Y (buying interest) is 92%, while the remaining 8% is influenced by other variables that are not discussed in this study.